2012
DOI: 10.1590/s0102-695x2011005000199
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of the sulfated polysaccharide from the vascular plant Halodule wrightii

Abstract: Abstract:A sulfated polysaccharide (SPSG) was successfully isolated from seagrass Halodule wrightii Asch., Cymodoceaceae, and its antioxidant and anticoagulant activities were investigated. The data presented here showed that the SPSG is a 11 kDa sulfated heterogalactan with a sulfatation degree of 20.63% and it also contains glucose and xylose. SPSG antioxidant activities were evaluated using several in vitro assays and the anticoagulant activity was evaluated by aPTT and PT tests. These assays suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…The results also indicate that galactose is the major monosaccharide component as detailed in Table 5. In comparison with other studies 21) , it was noted that some monosaccharides are commonly found in P. oceanica including glucose, galactose, xylose and the difference in the composition may be due to the extraction, the purification and the separation conditions or to environmental factors 22) . SEC/MALS/DRI was used to determine the distribution and range of molecular weight of PPO.…”
Section: Physico-chemical Characterizationmentioning
confidence: 69%
“…The results also indicate that galactose is the major monosaccharide component as detailed in Table 5. In comparison with other studies 21) , it was noted that some monosaccharides are commonly found in P. oceanica including glucose, galactose, xylose and the difference in the composition may be due to the extraction, the purification and the separation conditions or to environmental factors 22) . SEC/MALS/DRI was used to determine the distribution and range of molecular weight of PPO.…”
Section: Physico-chemical Characterizationmentioning
confidence: 69%
“…The antioxidant capacity assay is based on the reduction of molybdenum(VI) to molybdenum(V) by the sulfated galactan-rich fractions and the subsequent formation of a green phosphate/Mo(V) complex at acidic pH (Silva et al 2012). Tubes containing sulfated galactan-rich fractions and reagent solution (0.6 M sulfuric acid, 28 mM sodium phosphate, and 4 mM ammonium molybdate) were incubated at 95°C for 90 min.…”
Section: Determination Of Total Antioxidant Capacitymentioning
confidence: 99%
“…The presence of sulfated polysaccharides was determined in three species, of which, the Ruppia maritima sulfated polysaccharide was purified and its structure was characterized. 19 To date, the sulfated polysaccharide of Halodule wrightii has been characterized for its antioxidant and anticoagulant activities. 19 We reported the existence of the anti-inflammatory activity in seagrass Halophila ovalis methanol extract.…”
Section: Introductionmentioning
confidence: 99%
“…19 To date, the sulfated polysaccharide of Halodule wrightii has been characterized for its antioxidant and anticoagulant activities. 19 We reported the existence of the anti-inflammatory activity in seagrass Halophila ovalis methanol extract. 20 However, there is no single report about the biological activities of sulfated polysaccharides from seagrass H. ovalis until now.…”
Section: Introductionmentioning
confidence: 99%